Claims on the Existence and Reconstruction of as Suyuthi's Tafsir Majma' Bahrain - Ihsan, Mishbah Nur; Rofif, Ahmad Haidar (Proceedings of International Conference on Muslim Society and Thought, 2024)
The popularity of Suyuthi's expertise as a mufassir seems to have created its own space of authority in the discipline of tafsir. As a prolific scholar, of course the reading of it cannot be arbitrary and atomistic. At least there is an attempt to read that can integrate between his works, considering also the number of works he produced. One of Suyuthi's major works is the book al Itqan which discusses ulum al Quran. In the preamble of the book, Suyuthi explicitly expressed his intention to write a book of tafsir that is applicable to the methodology he offers in Itqan. Suyuthi envisioned a book of tafsir that was considered comprehensive and could gather all the ideas of ijtihad from his books. No one knows for sure what Suyuthi actually wanted to concretize in his dream of writing the Majma' al Bahrain tafsir book, nor has the manuscript of the book been found until now. One of the main ideas Suyuthi intended to write Majma' al Bahrain was to combine the riwayah and dirayah approaches. An attempt to grope Suyuthi's ideas departs from the assumptions narrated by Suyuthi himself in his books when introducing the book of Majma' Bahrain that failed to be written, as mentioned in the preamble of al Itqan and Qatf al Azhar. This article aims to conduct a reconstruction that is expected to adequately represent Suyuthi's ideas about the Majma' al Bahrain tafsir plan that he revealed in several of his books. The methodology that tries to be pursued is to elaborate and combine Suyuthi's works (both tafsir and methodology), to find a pre-discourse on Suyuthi's wish in the book of Majma' al Bahrain that was not done. For that purpose, the researcher has inventoried a number of Suyuthi's essays that are relevant to the discipline of tafsir as many as 13 books.